On the Wall Pressure Fluctuations induced by a Supersonic Jet over the Wing pressure side. Issue 1 (1st June 2022) - Meloni, S.; de Paola, E.; Curcio, L.; Camussi, R.
Abstract: Supersonic jet wing integrated configurations are expected to be relatively louder than subsonic installed configurations, increasing the wall pressure load transmitted inside the fuselage and stressing the wing/fuselage panels with very energetic and frequency localized supersonic effects. In this framework, a model-scale experimental investigation of an installed jet-wing configuration has been performed using a supersonic convergent-divergent nozzle interacting with a wing generated by a NACA4415 airfoil. The measurements have been carried out in the semi-anechoic chamber of the "G.Guj" Fluid Dynamic laboratory at the University Roma Tre. Wall pressure fluctuations are acquired at different axial locations in stream-wise and span-wise directions. Measurements are repeated for different wing radial positions and by varying the NPR between 2.2 and 2.6, thus exploring both over-expanded and under-expanded jet flow conditions. The flow features that characterize the different flow regimes were caught using the Background Oriented Schlieren (BOS) technique. Fluctuating pressure data, acquired with flush-mounted pressure transducers, were analysed in the frequency domain, considering a Fourier-based approach. A comparison of results obtained with an infinite flat plate has been used to highlight effects generated by the discontinuity related to the trailing edge.